Does Appliance Design Affect Treatment Outcomes of Class II Division 1 Malocclusion? A Two-Center Retrospective Study - Burçin Akan; Türkan Sezen Erhamza (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of this retrospective study was to compare the pre- and post-treatment values of patients treated with monoblock and twin-block appliances with the values of the skeletal Class I individuals.